Sugarboilers in Amsterdam: a database - Nováky, György (Uppsala University, 2018)
The datafile contains all persons in Gemeente Archief Amsterdam active in the sugar boiling business 1593-1715.

The dataset was originally published in DiVA and moved to SND in 2024.

Datafilen innehåller alla personer i Gemeente Archief Amsterdam som var aktiva inom sockersjudningsbranschen 1593-1715.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Sockersjudare i Amsterdam: en databas
Keywords: sugar trade; sugar trade; Early Modern Period; Early Modern Period; History; History; Sugarboilers; Sugarboilers; Amsterdam; Amsterdam; History and Archaeology; Historia och arkeologi